2019
DOI: 10.1016/j.jaci.2018.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Soil exposure modifies the gut microbiota and supports immune tolerance in a mouse model

Abstract: Our results provide evidence of the role of environmentally acquired microbes in alleviating against T2-driven inflammation, which relates to allergic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
129
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(137 citation statements)
references
References 78 publications
7
129
0
1
Order By: Relevance
“…31,32 In addition, there is evidence from murine models that exposure to microbes in house dust modulates intestinal microbiota and might, at least partially, mediate the effect on immune responses in the airways. 30,33 Whether this would also apply to human subjects remains unknown. There is evidence that environmental factors, such as dogs, can influence human gut microbiota composition, 30,34 but overall, this influence is thought to be limited.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 In addition, there is evidence from murine models that exposure to microbes in house dust modulates intestinal microbiota and might, at least partially, mediate the effect on immune responses in the airways. 30,33 Whether this would also apply to human subjects remains unknown. There is evidence that environmental factors, such as dogs, can influence human gut microbiota composition, 30,34 but overall, this influence is thought to be limited.…”
Section: Discussionmentioning
confidence: 99%
“…Human observations have been experimented in animal models. For example, mice housed in contact with soil or clean bedding had marked differences in the composition of small intestinal microbiota . The microbes acquired from the soil alleviated Th2‐driven inflammation, which is a prerequisite for allergic conditions.…”
Section: Human Microbiomementioning
confidence: 99%
“…In allergic asthma, altered gut microbiota of fetal age in mice has been reported to augment allergic sensitization. 1,2 Moreover, epidemiological studies have shown that the use of antibiotics and a modern lifestyle in infancy increase the prevalence of asthma. 3 However, despite the emerging evidence of the gut-lung axis, there is still a lack of insight into the relationship between gut microbiota and allergic airway inflammation.…”
Section: Altered Gut Microbiota By Azithromycin Attenuates Airway Infmentioning
confidence: 99%
“…8 In addition, we administered antibiotics only during the challenge period, but not during the sensitization period, which differed from previous studies' models that induced gut microbiota changes during the sensitization period. 1,8 Previous studies reported that the lower respiratory tract microbiota is also associated with asthma inflammation. However, our study revealed that the airway microbiome is too small in terms of biomass to have a substantial effect on airway inflammation.…”
Section: Altered Gut Microbiota By Azithromycin Attenuates Airway Infmentioning
confidence: 99%